2022
DOI: 10.26717/bjstr.2022.41.006616
|View full text |Cite
|
Sign up to set email alerts
|

"Inventing of Macrocyclic Formazan Compounds with Their Evaluation in Nano- Behavior in the Scanning Microscope and Chromatography"

Abstract: Cyclic Formazan was invented and prepared for the first time by researcher Dr. Nagham Aljamali was established in April 2021. Therefore, it is considered one of the developed and modern compounds, which is described by a lack of references and researches. Therefore, the researcher, Dr. Nagham prepared and created a series of these compounds and studied several applications, including biological, pharmaceutical studies, also as antifungal, antibacterial, and anticancer agents, and here in this research, cyclic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Studying of Nano-Application carried out via using Scanning Electron Microscopy (SEM) that appeared good results about nano-dimensions of the prepared compounds with the scanning microscope technology to find out the nano-dimensions of the compounds, whether they are suitable for medical applications. The results of the examination proved that it possesses nanoscale properties according to methods [32,52] that qualify it to be successful pharmaceutical compounds.…”
Section: Nano-studymentioning
confidence: 99%
See 1 more Smart Citation
“…Studying of Nano-Application carried out via using Scanning Electron Microscopy (SEM) that appeared good results about nano-dimensions of the prepared compounds with the scanning microscope technology to find out the nano-dimensions of the compounds, whether they are suitable for medical applications. The results of the examination proved that it possesses nanoscale properties according to methods [32,52] that qualify it to be successful pharmaceutical compounds.…”
Section: Nano-studymentioning
confidence: 99%
“…Some studies [12][13][14][15][16][17][18][19][20] have proven the effectiveness of triazole derivatives as anti-corrosion materials and materials used as stable dyes when linked to azo groups, and color-blocking groups that increase the intensity of color when dyeing [21][22][23][24][25]. Through the research it was concluded that when the three prepared compounds are combined [26][27][28][29] , they appear as a wonderful cathode that inhibits corrosion and is striped [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…GC-MS has been regarded as forensic substance identification because it is used to perform a 100% specific test which positively identifies the presence of a particular substance [9,10]. After identification of chemical structures and pharmacological activities of various flavanoids, their chemical structures can be modified by using computer-aided drug design programs, use them in nanoformulations, change their dosage and forms, modify or synthesize specific flavonoids with a stronger targeting strategy, lower toxic side effects and make them more adaptable to the complex physiological conditions of the human body [11].…”
Section: Introductionmentioning
confidence: 99%